Mechanism of Stimulation of Vasopressin Release during Beta Adrenergic Stimulation with Isoproterenol - Berl, Tomas (1974)
Recent studies have demonstrated that the antidiuresis associated with intravenous (i.v.) infusion of the beta adrenergic agonist, isoproterenol (ISO), is mediated by release of endogenous vasopressin. To examine whether beta-adrenergic stimulation causes vasopressin release by a direct cerebral action, ISO was infused into the carotid artery in a dose estimated to equal the amount of catecholamine reaching the cerebral circulation in the i.v. studies. This intracarotid infusion did not alter renal or systemic hemodynamics, urinary osmolality (Uosm) or free-water clearance (C(H(2)O)). Although renal perfusion pressure was maintained constant in all experiments i.v. ISO was consistently associated with a decrease in total peripheral resistance and systemic arterial pressure as cardiac output increased. To investigate whether the decrease in cerebral perfusion pressure with i.v. ISO might be responsible for vasopressin release, the carotid arteries were bilaterally constricted both above and below the carotid sinus to lower carotid perfusion pressure by a mean of 25 mmHg, a decrement comparable to that observed during i.v. ISO. Constriction of the carotid arteries above the carotid sinus did not affect Uosm or C(H(2)O), while constriction below the sinus was associated with an antidiuresis as Uosm increased from 155±25 to 385±58 mosmol/kg (P < 0.001) and C(H(2)O) decreased from 1.20 to −0.44 ml/min (P < 0.001). This antidiuresis was not significantly different from that observed during i.v. ISO. Since these results suggested that changes in autonomic neural tone from arterial baroreceptors are responsible for vasopressin release with i.v. ISO, studies were performed in animals with denervated baroreceptors. While sham-operated animals and animals with bilateral cervical vagotomy showed a reversible antidiuresis with i.v. ISO infusion, dogs with complete denervation of arterial baroreceptors did not show a significant alteration in renal water excretion (Uosm, 187 to 182 mosmol/kg and C(H(2)O), 0.59 to 0.74 ml/min). The results therefore indicate that ISO stimulates vasopressin release by altering baroreceptor tone rather than by a direct central or depressor effect of the catecholamine. These same baroreceptor pathways have been recently shown to be involved in the suppression of vasopressin release with norepinephrine and may well be the common pathway whereby nonosmotic stimuli control vasopressin release.